Study of Corporal Punishment in Schools in Indonesia, 1966-2014 - Nasution Nasution; Sugeng Harianto; Esa Putra Bayu Gusti Gineung Patridina; Izzatul Fajriyah; FX Sri Sadewo; Wasino; Arifeen Yama (Paramita: Historical Studies Journal, 2025)
Abstract: This study investigates the practice of corporal punishment in Indonesian schools across three major political periods—Sukarno, the New Order, and the Reform era—before implementing the Child-Friendly School Policy in 2014. Employing a historical method within a case study framework, this research draws on in-depth interviews with six purposively selected individuals who experienced corporal punishment during their school years. Findings reveal that corporal punishment was normalized in earlier eras to instill obedience and maintain classroom order. During the Sukarno and New Order periods, such punishment—ranging from beatings with rattan sticks and rulers to forced labor and public humiliation—was harsh and widespread. In contrast, the Reform era marked a gradual shift toward less severe and more symbolic punitive practices, reflecting the growing influence of child rights discourses. The introduction of the Child-Friendly School Policy in 2014 served as a pivotal policy intervention, significantly reducing the prevalence and severity of corporal punishment. Nonetheless, residual practices persist, indicating a gap between regulatory frameworks and actual implementation at the school level. This study highlights the urgent need for comprehensive pedagogical reform and targeted teacher training to eradicate corporal punishment and foster child-centered, non-violent educational environments. Abstrak: Penelitian ini mengkaji praktik hukuman fisik di sekolah-sekolah Indonesia pada tiga era politik yang berbeda—Era Sukarno, Orde Baru, dan Reformasi—sebelum diterapkannya Kebijakan Sekolah Ramah Anak pada tahun 2014. Penelitian ini menggunakan metode sejarah dengan desain studi kasus, serta melibatkan enam informan yang secara purposif dipilih karena memiliki pengalaman menerima hukuman fisik selama masa sekolah. Temuan menunjukkan bahwa hukuman fisik diterima secara luas dan dianggap normal pada era sebelumnya sebagai upaya pendisiplinan untuk menanamkan kepatuhan dan ketertiban. Pada masa Sukarno dan Orde Baru, praktik hukuman fisik seperti pukulan dengan rotan atau penggaris, kerja fisik paksa, dan penghukuman yang bersifat mempermalukan sangat lazim dan cenderung keras. Sebaliknya, pada era Reformasi terjadi pergeseran menuju bentuk hukuman yang lebih simbolik dan tidak terlalu berat, seiring dengan meningkatnya pengaruh wacana hak anak. Penerapan Kebijakan Sekolah Ramah Anak menjadi titik balik penting dalam mengurangi frekuensi dan intensitas praktik ini. Namun demikian, beberapa bentuk hukuman fisik tetap bertahan, yang menunjukkan adanya kesenjangan antara kebijakan dan praktik di lapangan. Studi ini menekankan perlunya reformasi pedagogis yang menyeluruh serta pelatihan guru untuk menghapuskan hukuman fisik dan mendorong terciptanya lingkungan pendidikan yang berpusat pada anak dan bebas dari kekerasan.